2020
DOI: 10.1152/ajpgi.00384.2019
|View full text |Cite
|
Sign up to set email alerts
|

Enlightening the frontiers of neurogastroenterology through optogenetics

Abstract: Neurogastroenterology refers to the study of the extrinsic and intrinsic nervous system circuits controlling the gastrointestinal (GI) tract. Over the past 5-10 years there has been an explosion in novel methodologies, technologies and approaches that offer great promise to advance our understanding of the basic mechanisms underlying GI function in health and disease. This review focuses on the use of optogenetics combined with electrophysiology in the field of neurogastroenterology. We discuss how these techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…There are various EP tools to record GI electrical activity such as afferent fiber recordings, single-unit recordings, multi-electrode arrays, field potentials, patch clamping, voltage-sensitive dyes, and calcium reporters. These tools are used to study the properties of enteric neurons, enteric glia, ICC, dorsal root ganglion (DRG), spinal neurons, spinal glia, and neurons and glia throughout the brain to determine the primary pathophysiological mechanisms of GI disorders [134]. EGG is one such tool that measures gastric myoelectrical activity and can be used to identify gastric arrhythmias [17,127,135].…”
Section: The Current State Of the Art In Gastrointestinal Ep Mappingmentioning
confidence: 99%
“…There are various EP tools to record GI electrical activity such as afferent fiber recordings, single-unit recordings, multi-electrode arrays, field potentials, patch clamping, voltage-sensitive dyes, and calcium reporters. These tools are used to study the properties of enteric neurons, enteric glia, ICC, dorsal root ganglion (DRG), spinal neurons, spinal glia, and neurons and glia throughout the brain to determine the primary pathophysiological mechanisms of GI disorders [134]. EGG is one such tool that measures gastric myoelectrical activity and can be used to identify gastric arrhythmias [17,127,135].…”
Section: The Current State Of the Art In Gastrointestinal Ep Mappingmentioning
confidence: 99%
“…The advantage of combining optical imaging and genetically encoded fluorescent sensors or activators provides the capability of targeting specific cell populations, increasing spatial and temporal resolution (Deisseroth, 2011). While initially conceived in the CNS, optogenetic techniques have proven invaluable in the study of other complex integrated cellular systems, including the GI tract (Boesmans et al, 2015(Boesmans et al, , 2018Johnson et al, 2020). In subsequent sections, we will review general optogenetic techniques and how they have been used to study the cellular systems underlying GI motility patterns.…”
Section: Debate On the Role Of Specific Cell Types In Gi Motilitymentioning
confidence: 99%
“…A decade after the development of optogenetics in neuroscience, neurogastroenterology has started to utilize optogenetics technology to study central and peripheral nervous systems manipulating gastrointestinal function. 73 The first time, Stamp et al by transplanting enteric neural cells expressing ChR into the distal colon of mice, found that bowl smooth muscle of mice innervated by neurons matured from transplanted enteric neural cells following light stimulation of ChR. 48 To address cell-type specificity of optogenetics, studies were done by selective targeting of cholinergic neurons 74 and calretinin cholinergic neurons 75 which expressed ChR, suggesting selective stimulation of ENS expressed ChR could be enough to modify gastrointestinal motility.…”
Section: Neurogastroenterologymentioning
confidence: 99%
“…It combats disorders in which a disrupted interplay occurs between the nervous system and gastrointestinal system. A decade after the development of optogenetics in neuroscience, neurogastroenterology has started to utilize optogenetics technology to study central and peripheral nervous systems manipulating gastrointestinal function 73 . The first time, Stamp et al by transplanting enteric neural cells expressing ChR into the distal colon of mice, found that bowl smooth muscle of mice innervated by neurons matured from transplanted enteric neural cells following light stimulation of ChR 48 .…”
Section: Neurogastroenterologymentioning
confidence: 99%